Financial crises: Past and future - Carmen M. Reinhart (American Enterprise Institute (AEI), 2018)
This working paper, based on Carmen Reinhart's Adam Smith Lecture at the 60th NABE Annual Meeting in September 2018, takes a selective global tour of some of the prominent economic and financial risks in advanced, emerging, and low-income developing economies.
Keywords: A; 330; debt crisis; 2008 financial crisis; economic crisis; developing countries